A descriptive study on the users and utility of HIV/AIDS helpline in Karnataka, India - Glory Alexander; Chitra Kanth; Remya Thomas (Wolters Kluwer Medknow Publications, 2011)
Background: Globally, Telephone help-lines have proved their utility in several crisis situations. They were introduced in India for helping persons in need of counseling or emergency care such as victims of suicide, cardiac arrests, etc. The utility of such help-lines in HIV/AIDS has not been established .Hence this study done in ASHA Foundation, Bangalore. Objectives: To determine the characteristics of persons who access the HIV/AIDS helpline. To determine the reasons for calling the helpline. To identify the gaps in the provision of this service. Materials and Methods: Details on all calls received on ASHA Foundation's HIV/AIDS help line during the period January 2007 to December 2008, were entered on MS excel worksheet and analyzed using the SPSS software. Results: Majority of callers are male, are in the age group of 20-39 years and educated. The most common reasons for calling the helpline were for HIV testing, information about HIV/AIDS, care and support services and referrals to other services not linked to HIV/AIDS. Reasons for calling were linked to risk ( HIV testing, condom use etc) in younger persons, and to avail of care and support services in the older age-group. Conclusions: The main users of the HIV/AIDS helpline are urban ,young, educated males.